Effects of Pulmonary Vascular Resistance Index on Oxygen Saturation in Patients with Atrial Septal Defect - Supomo, Supomo (Jurnal Kedokteran Brawijaya, 2020)
Atrial septal defect (ASD) is a congenital lesion in atrium septum. The lesion may cause pulmonary hypertension due to the high pressure in the right ventricle. This condition leads to cyanosis in ASD patient, but the pathophysiology of cyanosis in ASD patient is still unknown. This study aimed to identify the pathophysiology of cyanosis in ASD patients using the Pulmonary Vascular Resistance index (PVRi). The design of this study was retrospective cohort study. The data used in this study were the results of right heart catheterization procedure taken from forty ASD patient medical records at Dr. Sardjito general hospital. The exclusions criteria were the history of previous vasodilator administration and incomplete medical records. The median age of the patients was 30 (18-55) years old. The mean of the Qp/Qs ratio was 1.210 (0.57-6.33). Optimum oxygen saturation was found in vessel leaving the heart. The PVRi median is 61.98 (-15.58-676.64). The PVRi has a significant correlation with oxygen saturation, except in the right atrium. There is a significant correlation between PVRi and oxygen saturation in various heart chambers. Pathophysiology of cyanosis in ASD patients is central cyanosis.